Chemical constituents from the starfish Protoreaster nodosus - Vu Anh Tu, Pham Thi Mai Huong, Nguyen Phuong Thao, Tran Thi Hong Hanh,; Thanh, Nguyen Van; Cuong, Nguyen Xuan; Young Ho Kim, Chau Van Minh, Nguyen Hoai Nam, Do Cong Thung, Phan Van Kiem, (Vietnam Journal of Chemistry, 2015)
Using various chromatographic methods, a glycosylated polyhydroxysterol nodososide (1) and three polyhydroxylated sterols (25S),5α-cholestane-3β,6α,8β,15α,16β,26-hexol (2), (25S),5α-cholestane-3β,6α,7α,8β,15α,16β,26-heptol (3), (25S),5α-cholestane-3β,4β,6α,7α,8β,15α,16β,26-octol (4), were isolated from the methanol extract of the starfish Protoreaster nodosus. The structural elucidations were done using 1D and 2D-NMR experiments and comparison of the NMR data with reported values.